Impact of Stock Recommendations on Finnish Stock Market - Luomala, Iiro (My University, 2019)
Stock recommendations have gain interest, and became more important over the past years. Thus, brokerage houses are spending more and more money to examine companies and then, investors are following those recommendations. Hence, the purpose of the thesis is to examine whether stock recommendations may generate positive abnormal returns. Earnings generated by stock analysts’ recommendations can be considered to be an anomaly, that is, a deviation from the efficient market hypothesis. According to Fama’s (1970) efficient market hypothesis, all information should be available and new information should reflect to prices immediately when the new announcement is given. Stock recommendations can be divided into five groups based on stock analysts’ recommendations; strong buy, buy, hold, sell and strong sell recommendations. Based on analysts’ consensus recommendations, five portfolios are formed, whose performance is under investigation. When a company is given a recommendation, it is added to a specific portfolio and the company’s return is calculated. When the consensus recommendation changes, the company will be moved to another portfolio and the return will be recalculated. The thesis studies stock prices and returns of 62 companies from the Finnish stock market between 2010 and 2018. The hypothesis of the thesis is tested by several statistical methods, such as an ordinary least square and panel data methods. The results of both statistical methods are corresponding, thus strong buy, buy and unexpectedly, also strong sell recommendations, generate positive abnormal returns while sell recommendations produce negative abnormal returns during the observation period. Neither panel data methods nor OLS regression could find any statistically significant results for hold recommendations.
Keywords: stock recommendation, abnormal returns; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance